Entre linhas e nós : um olhar da educação ambiental sobre o currículo na comunidade quilombola de Mata Cavalo - Areval, Amanda Martíns de Espíndula (2018)
The construction of this research was woven by Community Quilombola de Mata Cavalo, located in the municipality of Nossa Senhora do Livramento, Mato Grosso. In order to understand the importance of the curriculum in the context of a quilombola school. We write the writing of this dissertation with the eyes and senses attentive to the education and the curriculum in the quilombo, reflecting on the importance of the collective construction of knowledge of this Learning Community, with Environmental Education as a fundamental line. The methodology chosen was Gauthier's sociopoetics, which allowed us to involve a research group in the exchange of knowledge and senses, uniting CONCEPTS with AFFECTS, the CONFETTS, casting new glances over a school within the quilombo. Focusing on environmental education, quilombola education and the curriculum, it was possible to understand the processes of collective construction of a curriculum of life, thought with and by the quilombola community. During the writing of the chapters was described the history of the quilombos in Brazil, the quilombo of Mata Cavalo and their fight for the right to education within his territory, where it can be seen that the interweaving of Quilombola Education and Environmental Education, through the embroidery of Sustainable Schools, brings the drawing of the EU-CURRICULUM (the knowledges and doings of the people) with the OTHER-MANAGEMENT (cultural relations / local ethnography) and the entanglement with the WORLD-SPACE (the territorial struggle), forming a curriculum of phenomenological life and, therefore, post-critical. A curriculum that works on the issue of culture, interculturality and identity, without neglecting the quilombola struggle, which is also territorial and, thus, an environmental struggle. The construction of the curriculum of life means considering all the interculturality that exists in the quilombo, materializing its culture and its knowledge as a way of fighting and resisting before an excluding and intentional system that still ignores them today. Bringing the elaboration of educational tactics to be developed within the quilombo; new projects, new dreams, with the strength of the hands and lines of its history.